Hospital Management Support to Enhance Nursing Excellence: A Health Law Perspective - Irawati, Jovita (PT. BERBAGI TEKNOLOGI SEMESTA, 2024)
The management team's role in the hospital environment significantly impacts nurses' behavior in providing excellent patient care. Therefore, this study aimed to examine the effect of the management team on nurses' job enjoyment, medical affairs, and excellent care in Jakarta hospitals. In addition, it investigated the impacts of nurses' job enjoyment and medical affairs on excellent patient care. This study used a quantitative approach and survey method involving 200 hospital nurses in Jakarta. Questionnaire data were analyzed using variance-based structural equation modeling. Consequently, all the hypotheses were accepted. The management team affects nurses' job enjoyment, medical affairs, and excellent care in Jakarta hospitals. Additionally, nurses' job enjoyment and medical affairs contribute to excellent care. These findings confirm the importance of policies encouraging hospital management involvement in creating a better work environment to improve patient care.